Hierarchically assembled silver nanoprism-graphene oxide-silicon nanowire arrays for ultrasensitive surface enhanced Raman spectroscopy sensing of atrazine. (February 2022) - Daoudi, Kais; Gaidi, Mounir; Columbus, Soumya; Shameer, Mohammed; Alawadhi, Hussain
Abstract: Exploration of novel strategies for fabricating SERS substrates attracted enormous research potential as achieving high sensitivity, reproducibility along with cost effectiveness is really challenging. Herein, we have fabricated hierarchical silver nanoprism/graphene oxide/silicon nanowire (Ag/GO/SiNWs) arrays as surface-enhanced Raman scattering (SERS) sensors for the effective detection of atrazine. Homogenous and vertically aligned SiNWs have been successfully synthesized using silver assisted chemical etching. Further, Ag/GO/SiNWs arrays were assembled by subsequent spin-coating of GO followed by drop-casting deposition of Ag nanoprisms. Micro-structural properties of as-fabricated nano-arrays have been well examined by scanning electron and atomic force microscopic techniques. Nanowire bunches have been decorated by GO layers; which further facilitates homogenous deposition of Ag nanoprisms. Using rhodamin 6G as probe molecule, high SERS activity and excellent reproducibility of as-fabricated substrates have been demonstrated. High efficiency of 3.2 × 10 8 and was obtained for the fabricated sensors; attributed to the synergetic charge transfer between GO and Ag nanoprisms on high surface area Si nanowires. Charge transfer mechanism that leading to enhanced surface plasmon resonance effect of the as-fabricated array was established as well. Further, these low cost Ag/GO/SiNWs sensors exhibited ultrasensitive detection of pollutants such as methylene blue and atrazine residues down to picomolar levels; these can serve as potential chemical sensors for rapid monitoring of environmental pollutants in trace levels. Graphical abstract: Image 1 Highlights: Novel silver nanoprism-Graphene Oxide-Silicon Nanowire sensors were fabricated. Micro-structural characteristics of sensor were well elucidated. Nano-arrays exhibited superior sensitivity and reproducibility. SERS enhancement factor of 3.2 × 10 10 was obtained. Hierarchial structures detected atrazine down to picomolar levels.